Sanksi Pidana Denda Dan Manfaatnya Bagi Pelaku Tindak Pidana Pelanggaran Menurut Buku III KUHP - Risma Wanti; Imam Verdinand; Annisa Dwi Salimah; Saryanto; M.Rafi Akbar (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
New sanctions for liquidation if other sanctions can't solve the problem. According to article 503 of the Code, interference in the vicinity of a building for the conduct of authorized worship or interruption in the proximity of the building for conducting authorized service is punishable by imprisonment for a maximum of three days or a maximum fine of two hundred twenty-five rupees. According to Book III of the Covenant, the profits obtained by the perpetrator of a criminal offence are as follows: penal sanctions fine preserving the good name or honour of perpetrators of the offence and does not create a bad impression on the person concerned; penal sanction fine prevents bad influence and prevents stumbling.